2009
DOI: 10.1021/jp9031833
|View full text |Cite
|
Sign up to set email alerts
|

Catalysis Effects of Water Molecules and of Charge on Intramolecular Proton Transfer of Uracil

Abstract: In this work, the three most stable uracil isomers (U1, U2, and U3) and their neutral, positive, and negative charged multihydrates are chosen as research objects to investigate the tautomeric process between the most stable uracil, U1, and its two minor stable isomers, U2 and U3. By the study, deeper insight can be obtained regarding point mutations induced by uracil deformation. Toward the target, the activation energies of the intramolecular proton transfer (tautomeric process) as well as the catalysis effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
40
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 55 publications
(119 reference statements)
5
40
0
Order By: Relevance
“…Although it was possible to converge this calculation, it did not yield a single-proton TS. These findings are in agreement with previous studies on the mechanism of the keto-enol tautomerism of nucleic acid bases, [19,[44][45][46] pyridine derivatives, [38][39][40][41] and other compounds [43,51] in aqueous media. It was found that the tautomerization reactions proceed preferentially by a multiple proton-transfer mechanism with the assistance of two to three water molecules.…”
Section: Calculationssupporting
confidence: 93%
See 2 more Smart Citations
“…Although it was possible to converge this calculation, it did not yield a single-proton TS. These findings are in agreement with previous studies on the mechanism of the keto-enol tautomerism of nucleic acid bases, [19,[44][45][46] pyridine derivatives, [38][39][40][41] and other compounds [43,51] in aqueous media. It was found that the tautomerization reactions proceed preferentially by a multiple proton-transfer mechanism with the assistance of two to three water molecules.…”
Section: Calculationssupporting
confidence: 93%
“…First, the canonical diketo form of uracil is changed to a keto-enol form (3,4-U), which is a fast stepwise process. [19,47,50] The 3,4-U form is then transformed into the rare 3,5-U tautomer. The organic solvents could act as catalysts in the formation of this rare tautomer.…”
Section: Isotopic Exchange Of the 5-h Of Uracil In Organic Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the optimized structures at DFT-D level, the author calculate the wavefunctions at the B3LYP/6-311+G(d) level of theory, then AIM theory which has been used to successfully determine intermolecular interactions of different systems is used in these systems. [30][31][32][33][34][35][36][37][38][39] In the AIM analyses, The transition state between chemisorption and physisorption of CO 2 have been investigated using the complete LST (linear synchronous transit)/QST (quadratic synchronous transit) method 41 implemented in DMOL3 code. The electron distribution and transfer mechanism are determined using the Mulliken method.…”
Section: Methodsmentioning
confidence: 99%
“…We suggested the following mechanism of isotopic exchange (Scheme 2): The exchange reaction involves a very rare uracil tautomer, which has an sp 3 hybridized carbon atom in position 5. First, the canonical diketo form of uracil is changed to a ketoenol form (3,4-U), which is a fast stepwise process [27][28][29] . The 3,4-U form is then transformed to the rare 3,5-U tautomer.…”
mentioning
confidence: 99%